Olika typer av täckning och samodling och dess påverkan på antalet skadegörare i en Pak choi odling - Mattsson, Caroline (2006)
The purpose of this report is to examine the possibilities to decrease the number of insects and other pathogens in a crop of pak choi (Brassica rapa), grown with different types of cover and living mulches. Included in the report is a study of literature where amongst others, a summary on the vegetable pak choi and theories of living mulches and different kind of covers are to be found. To examine the amount of predators in the field, traps were used. During the autumn 2002 the tests were conducted in Alnarp. The pak choi and the living mulches were planted/sawn at the same time, the different covers were also applied at this time. The total experiment was divided into six different treatments (plus control) of which three were with covers and three were with living mulches. Once a week the number of leaves, the height and damages were read on ten of the plants from each parcel. Because of generally bad growth in the field, soil samples were taken after harvesting of the plants. The report of the analysis showed a major lack of nitrogen in the field. Since nitrogen is of great importance when growing cabbage the deficiency of nitrogen turned out to be the major limitation of the results. The three covers were cut grass, cut clover and cloth of fibre. Where the parcels were covered with clover or grass the plants visually seemed more healthy and vigorous than the other plants. This is probably due to the fact that cut of clover and grass continuously releases nitrogen. The improved condition of these plants also seemed to make the plants more resistant against insects and other patogens than the plants which were even more weakened by the deficiency of nitrogen. Another positive effect of the cover with clover was the visual impression that the predators seemed to be more frequently occurring in the clover than in the other parcels.